Effects of a therapeutic lifestyle modification intervention on cardiometabolic health, sexual functioning and health-related quality of life in perimenopausal Chinese women: protocol for a randomised controlled trial - Wang, Yuru; Miao, Xiaoling; Viwattanakulvanid, Pramon (BMJ open, 2024)
IntroductionPerimenopause is a critical transitional period in reproductive ageing. A set of physiological and psychological changes can affect perimenopausal women’s quality of life and further threaten their older adult health conditions. In China, less than one-third of midlife women with menopausal symptoms have actively sought professional healthcare. Regarding the public health significance of comprehensive menopause management, the current study aims to investigate the effects of a therapeutic lifestyle modification (TLM) intervention on cardiometabolic health, sexual functioning and health-related quality of life among perimenopausal Chinese women.Method and analysisA randomised controlled trial with two parallel arms will be conducted at the gynaecology outpatient department of Yunnan Provincial Hospital of Traditional Chinese Medicine in China. 94 eligible perimenopausal women aged between 40 and 55 years will be recruited for the study. The TLM intervention consists of four elements: menopause-related health education, dietary guidance, pelvic floor muscle training and Bafa Wubu Tai Chi exercise. Participants will be randomly assigned (1:1) to receive either the 12-week TLM intervention or routine care via stratified blocked randomisation. The primary outcome is quality of life; secondary outcomes of interest include sexual functioning and cardiometabolic health. The outcome measures will be assessed at baseline and post-intervention. To explore the effects of the intervention, linear mixed models will be applied to test the changes between the two groups over time in each outcome based on an intention-to-treat analysis.Ethics and disseminationThe Research Ethics Review Committee of Chulalongkorn University (COA No 178/66) and the Medical Ethics Committee of Yunnan Provincial Hospital of Traditional Chinese Medicine (IRB-AF-027-2022/02-02) approved the study protocol. Written informed consent will be obtained from all participants. Results will be published in peer-reviewed journals and disseminated through conferences.Trial registration numberChiCTR2300070648.